Linking Global CGE Models with Sectoral Models to Generate Baseline Scenarios: Approaches, Challenges, and Opportunities - Delzeit, Ruth; Beach, Robert H.; Bibas, Ruben; Britz, Wolfgang; Chateau, Jean; Freund, Florian; Lefevre, Franziska Schuenemann; Sulser, Timothy B.; Valin, Hugo; van Ruijven, Bas; Weitzel, Matthias; Willenbockel, Dirk; et al. (Center for Global Trade Analysis, Department of Agricultural Economics, Purdue University, 2020)
When modelling medium and long-term challenges we need a reference path of economic development (the so-called baseline). Because sectoral models often offer a more fundamental understanding of future developments for specific sectors, many CGE modeling teams have adopted different kinds of linking approaches to sectoral models to generate baselines. We systematically compare and discuss approaches of linking CGE models for the baseline calibration procedure, and discuss best practices and pitfalls. We identify different types of linking approaches which we divide into a) links with partial equilibrium models, and b) links with non-economic models. These two types of linking approaches are then analyzed with respect to e.g. the degree of linkage, information exchanged, as well as compromises in aggregations and definitions. Based on this, we discuss potential drawbacks and conclude with suggestions for best practices and research recommendations.